Analisis Anak Berkebutuhan Khusus, Identifikasi Dan Implementasi Pendidikan Inklusi Di Sekolah Dasar Kabupaten Bungo - Zikrillah Zikrillah; Erwin Gunawan; Opi Andriani (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research aims to describe the identification and implementation of inclusive education for Children with Special Needs (ABK) in elementary schools in Bungo Regency. This research uses a descriptive method with a qualitative approach. Data collection was carried out through direct observation and interviews with participants. The subjects of this research were elementary school teachers in Bungo Regency, which consists of five districts or cities totaling 15 elementary schools. The results of the research findings include: (1) the disorders of students with special needs in 8 elementary schools spread across Bungo Regency are relatively the same, namely slow learning and mild mental impairment, (2) the implementation of inclusive education in elementary schools in Bungo Regency is not going well, and (3) obstacles to the implementation of inclusive education are the lack of facilities and infrastructure owned by schools and the costs for providing inclusive education facilities are relatively small, teachers' understanding of students with special needs is still very minimal.